Pinning of elastic ferromagnetic/antiferromagnetic interfaces in phase-separated manganites - Niebieskikwiat, Dario Gabriel; Sanchez, Rodolfo Daniel (IOP Publishing, 2012)
Fil: Niebieskikwiat, Dario Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad San Francisco de Quito; Ecuador